Faces A black - and - white book - Lemon Ribbon Studion (London Penguin Random House, 2019)
Hello, Friendly faces ! Designed to support a baby's developing eyesight, this high - contrast book will engage and delight young children from birth upwards
Scientific Notions
Keywords: Science